2019
DOI: 10.1038/s41598-018-37778-y
|View full text |Cite
|
Sign up to set email alerts
|

Induced vergence-accommodation conflict reduces cognitive performance in the Stroop test

Abstract: Interaction mechanisms between cognition and binocular motor control in reading saccades remain unclear. In this study we examine objectively saccades and fixations parameters during the Stroop test, involving three different levels of cognitive demand (reading, color denomination and interference). In addition, we experimentally induce accommodation and vergence conflicts during the different tasks. Twenty-one visually normal subjects (age 20.9 ± 1.45) performed the Stroop test in three different randomized c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 58 publications
1
31
0
Order By: Relevance
“…The results favor the hypothesis previously proposed by our lab: that disconjugate drifts arise from poor vergence control 13 , 57 . Further, our lab has previously shown that experimental induction of vergence/accommodation mismatch negatively impacts disconjugate post-saccadic drifts 27 . Indeed, the present study argues that these vergence velocity abnormalities and disconjugate post-saccadic drifts are related.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The results favor the hypothesis previously proposed by our lab: that disconjugate drifts arise from poor vergence control 13 , 57 . Further, our lab has previously shown that experimental induction of vergence/accommodation mismatch negatively impacts disconjugate post-saccadic drifts 27 . Indeed, the present study argues that these vergence velocity abnormalities and disconjugate post-saccadic drifts are related.…”
Section: Discussionmentioning
confidence: 98%
“…Indeed, previous studies have shown that when a mismatch of vergence and accommodation is induced experimentally (with the use of prisms or spherical lenses), saccades become more disconjugate (divergent), and the correlation between intra-saccadic disconjugacy and the post-saccadic disconjugacy drift weakens. Therefore, residual disparities during fixation occur, which would interfere with cognition and reading tested with the Stroop test 27 . Saccades themselves are necessary to move the eyes from one word to the next across a line of text.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the previous results, they explained that viewing three-dimensional content requires viewers to use more cognitive resources for processing three-dimensional information compared to two-dimensional content and that eyestrain is really brain strain, indicating cumulative cognitive load. Another previous study (Daniel & Kapoula, 2019) investigating for visually normal young participants indicated an interplay between vergence accommodation conflict and cognitive load and the link between cognition and high quality of single binocular vision. In addition, as shown in a recent review (Orru & Longo, 2019), visual input relates to working memory as well as auditory input, which is one of premise of Cognitive Load Theory.…”
Section: Introductionmentioning
confidence: 91%
“…These observations corroborate the effect of defocus on visual demands. In addition, the vergence-accommodation conflict has been shown to interfere with cognitive executive functions [92]. It is speculated that the neural correlates between cognitive control and the vergence-accommodation coupling partially overlap at the level of the frontal and parietal lobes.…”
Section: Plos Onementioning
confidence: 99%